Les comités de suivi de thèse comme lieux de mobilisation de savoirs incorporés ou en cours d’incorporation - Anne Jorro; Fabienne Saboya (Éducation et Socialisation)
The creation of follow-Up PhD committees in the training of PhD students in French higher education in 2016 made possible to inaugurate a space for dialogue between a doctoral student and peers on the experience of his doctoral path and his research work. This institutional device little invested in research holds promises from the point of view of learning, since the doctoral student exchanges with researchers and learns to communicate on his research work. The object of the research is to understand the formative dimension of CST, to understand what meeting with external researchers allows from the point of view of incorporated knowledge. A qualitative survey was conducted with fourteen doctoral students and three doctors in an educational science laboratory in order to identify and understand the specificity of the knowledge incorporated by them.